Experimental analysis into the main artery of 2 chamber heart model during cardiac cycle - Loh, Quo Liang (2013)
Regarding to the report from World Health Organization (WHO), the most killer disease throughout the world is cardiovascular disease. There are millions of people deaths because of this disease every year. So, it is important to study the blood pumping mechanism in human body and what is the reason causing this device damage or fail to operate normally in detail. The objective of this study is to develop a heart model for investigating the patterns of fluid flow, and blood velocity diastolic. This heart model is able to observe the fluid flow pattern in left and right ventricle in a pressurized pulsate flow. A detail on fabrication, limitation, future improvement, and problem faced of heart model are discussed in this study. The whole system will be conduct in a close system which operated by using the combination of motor, and syringe. The results showed a relationship between heart beat, velocity, and blood vessel diameter especially for inferior, and superior vena cava can be establish. The result also proved that the relationship between heart beat and the velocity, and the difference of pressure between atrium and ventricle are directly proportional. Additionally, the relationship between vortex formation and septum in the heart chamber can be established at the end of this study. In conclusion, this study had succeeded to produce an equation relates to the velocity, diameter and heart beat in inferior, and superior vena cava. This result can contribute to future heart study as well as application in medical field.